Peran Ketua Tim Dengan Kinerja Perawat Pelaksana Dalam Pendokumentasian Asuhan Keperawatan - Ritanalis, Theresia; Maryani, Lidya; Sinaga, Herwinda (STIKES Karya Husada Kediri, 2024)
Abstract The quality of nursing services is strongly influenced by the process, role and function of nursing service management in this case the role is owned by the team leader. Meanwhile, the performance of implementing nurses in documenting nursing care is an integral part of efforts to improve the quality of nursing services. This study aims to determine the relationship between the role of the team leader and the performance of implementing nurses in documenting nursing care in the inpatient room of St. Antonius Hospital Pontianak. The research method in this study is a type of quantitative research descriptive correlation design with a cross-sectional approach. Subjects in the study were 105 nurses using total sampling technique so that the sample was as much as the population. Data collection using a team leader role questionnaire and nurse performance in documenting nursing care that has been tested for validity and reliability. The results showed that most of the respondents stated the role of the team leader and the performance of executive nurses in documenting nursing care in the good category. And based on the results of statistical analysis using the Fisher Excact test obtained a value of p = 0.002 where p <α (0.005) which means Ho is rejected Ha accepted. The conclusion is that there is a significant relationship between the role of the team leader and the performance of the executive nurse in documenting nursing care. Suggestions are submitted so that in the future the management, especially the nursing field, can create a work program to improve skills and leadership (Leadership) for team leaders through nursing leadership workshops (leadership nursing), with specific activities namely skills and leadership in the process of documenting nursing care